Preparation method of ceramic particle reinforced high-temperature alloy wear-resistant coating of boiler water-cooled tube

Through atmospheric plasma spraying and laser remelting treatment, a high-temperature alloy wear-resistant coating strengthened by ceramic particles was prepared, which solved the problems of complex processes and difficult industrialization in the prior art, and achieved high wear resistance and ability of boiler water-cooled pipes. Controlled deposition.

CN119392157APending Publication Date: 2025-02-07YANGZHOU UNIV

Patent Information

Application Number
CN202411599912.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is complicated when preparing the wear-resistant coating of boiler water-cooled pipe high-temperature alloy, and requires high laser beam output accuracy and stability, and it is difficult to achieve large-scale industrial production.

Method used

Atmospheric plasma spraying NiCr-based composite powder was used, coarse treatment and ball milling were mixed, followed by atmospheric plasma spraying and laser remelting treatment to form a high-temperature alloy wear-resistant coating strengthened by ceramic particles.

Benefits of technology

The preparation process is simplified, the bonding force between the coating and the substrate is improved, the wear resistance of the boiler water-cooled pipe is significantly improved, and the controllable deposition of the wear-resistant coating of high-performance ceramic particle-strengthening high-temperature alloy is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392157A_ABST
    Figure CN119392157A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ceramic particle reinforced high-temperature alloy wear-resistant coating of a boiler water-cooled tube. The preparation method comprises the following steps: carrying out roughening treatment on a matrix; the prepared NiCr powder and ZrB2 powder are subjected to high-energy ball milling and mixing, drying is conducted after treatment, and dried NiCr-based composite powder is obtained; niCr-based composite powder is sprayed through atmospheric plasma, and a composite coating with the thickness ranging from 200 micrometers to 300 micrometers is deposited on the roughened surface of the base body; the composite coating is subjected to remelting treatment, and a remelting coating is formed on the surface of the base body; wherein the matrix is 304 stainless steel, and the composition proportions of the NiCr powder and the ZrB2 powder are as follows: 80-99 wt% of NiCr and 1-20 wt% of ZrB2 respectively; by means of the method, the wear resistance of the coating is remarkably improved, and controllable deposition of the high-performance ceramic particle reinforced high-temperature alloy wear-resistant coating is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal spraying and surface engineering, and in particular relates to a method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating of a boiler water-cooling tube. Background Art

[0002] As an important pipeline in the boiler, the water-cooling tube works in a harsh environment of high temperature, high pressure, flue gas corrosion and erosion for a long time. The high-speed airflow carries solid materials for circulation and combustion in the furnace, making the water-cooling tube extremely susceptible to serious fly ash wear. Leakage or burst caused by thinning of the tube wall not only seriously interferes with the normal operation of the boiler, but also creates huge production safety hazards. According to statistics, about half of the accidental shutdowns each year are attributed to this. The failure of water-cooling tubes has become a technical problem that urgently needs to be solved in the safe operation of the boiler.

[0003] At present, the main methods of protecting water-cooled pipes are to install anti-wear baffles and deposit wear-resistant coatings. For example, the invention patent with the announcement number CN111690928 B discloses "a method for preparing a high-efficiency and low-dilution coating for water-cooled wall tubes of boilers", which uses three types of laser collaborative cladding to prepare water-cooled pipe wear-resistant coatings. Although the coating prepared by this method has strong bonding strength and low matrix dilution rate, the method is complicated and has high requirements for laser beam output accuracy and stability, which is not conducive to large-scale industrial production. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above and / or existing problems in the prior art in preparing the wear-resistant coating of the high-temperature alloy of the boiler water-cooling tube, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-temperature alloy wear-resistant coating reinforced with ceramic particles for a boiler water-cooling tube. The preparation process is simple, and the controllable deposition of the high-temperature alloy wear-resistant coating is achieved, thereby enhancing the bonding strength between the wear-resistant coating and the outer wall of the water-cooling tube, and significantly improving the wear resistance of the boiler water-cooling tube.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating for a boiler water-cooling tube, comprising the following steps: Roughening the substrate; The prepared NiCr powder and ZrB2 powder are mixed by high-energy ball milling, and dried after treatment to obtain a dried NiCr-based composite powder; The NiCr-based composite powder is sprayed by atmospheric plasma to deposit a composite coating with a thickness of 200 to 300 μm on the roughened substrate surface; The composite coating is subjected to a remelting treatment to form a remelted coating on the surface of the substrate; The matrix is ​​304 stainless steel, and the composition ratios of NiCr powder and ZrB2 powder are 80-99 wt% NiCr and 1-20 wt%, respectively.

[0008] As a preferred embodiment of the preparation method of the present invention, the specific steps of the roughening treatment are: The impurities of the substrate are ultrasonically cleaned with anhydrous ethanol, and then dried and sandblasted to obtain a sandblasted and roughened substrate.

[0009] As a preferred embodiment of the preparation method of the present invention, the sandblasting roughening treatment uses brown corundum sand with a particle size of 24 mesh, the sandblasting pressure is 0.6 MPa, the sandblasting angle is 60°, and the roughness of the substrate after roughening is controlled at 2~8 μm.

[0010] As a preferred embodiment of the preparation method of the present invention, planetary ball milling is adopted during ball milling, the mass ratio of grinding balls to powder is 1:1, three grinding balls with different diameters are used, and the number ratio of the three grinding balls from large to small diameters is 2:5:3, the rotation speed is 600 r / min, the residence time after a single operation is 10 min, the total ball milling time is 8 h, and BF-300 binder is added at a uniform speed during the ball milling process.

[0011] As a preferred embodiment of the preparation method of the present invention, the average particle size of the NiCr powder is 45-80 μm, and the average particle size of the ZrB2 powder is 0.7-1 μm.

[0012] As a preferred embodiment of the preparation method of the present invention, the drying temperature is 80° C. and the drying time is 6 to 8 h.

[0013] As a preferred embodiment of the preparation method described in the present invention, the parameters of the atmospheric plasma spraying are as follows: current 500 A, Ar gas flow rate 40 L / min, H2 flow rate 6 L / min, powder feeding rate 2 g / min, spraying distance 100 mm, spray gun moving rate 200 mm / min, and compressed air is used to cool the stainless steel substrate during the spraying process.

[0014] As a preferred embodiment of the preparation method of the present invention, it also includes the following steps: placing the coating after atmospheric plasma spraying on a temperature field auxiliary heating platform, setting the heating temperature to 300°C and performing laser remelting treatment on the coating at this temperature.

[0015] As a preferred embodiment of the preparation method of the present invention, during the laser remelting process, a vibration with a frequency of 20 kHz and an amplitude of 5 μm is applied to the stainless steel substrate.

[0016] As a preferred embodiment of the preparation method of the present invention, during the laser remelting treatment, the laser power is 500-900 W, the scanning speed is 1000 mm / min, the overlap rate is 40%, and Ar gas with a flow rate of 6 L / min is introduced as a protective gas during the remelting process. The remelted coating is slowly cooled to room temperature together with the heating platform.

[0017] Compared with the prior art, the present invention has the following technical effects: simple preparation, introduction of hard boride as an added phase to replace carbide in traditional wear-resistant coatings, successful reduction of the content of oxide impurities generated during coating deposition, and coordinated remelting effect of high-energy laser beam. The prepared coating has refined organization, dense structure, and low porosity (0.65%). Observation of cross-sectional SEM images shows that laser remelting effectively repairs pores and cracks left during atmospheric plasma spraying, and the mechanical bonding between the coating and the substrate is transformed into a metallurgical bonding. The use of the present invention significantly improves the wear resistance of the coating, and realizes the controllable deposition of high-performance ceramic particle-reinforced high-temperature alloy wear-resistant coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 Schematic diagram of the atmospheric plasma spraying system in Example 1 of the present invention.

[0019] Figure 2 This is a schematic diagram of the ultrasonic vibration laser remelting system in Example 1 of the present invention, wherein 1 is a laser generator, 2 is a protective gas channel, 3 is a heating plate, 4 is a remelted coating, 5 is a substrate, 6 is an unremelted coating, 7 is a laser vibrometer, and 8 is an ultrasonic vibration device.

[0020] Figure 3 This is a microscopic morphology of the composite powder in Example 1 of the present invention.

[0021] Figure 4 This is a microscopic morphology of the cross section of the coating after atmospheric plasma spraying in Example 1 of the present invention.

[0022] Figure 5 This is a microscopic morphology of the cross section of the coating after laser remelting in Example 1 of the present invention.

[0023] Figure 6 This is a microscopic morphology of the composite powder in Example 2 of the present invention.

[0024] Figure 7 This is a microscopic morphology of the cross section of the coating after laser remelting in Example 2 of the present invention.

[0025] Figure 8 This is a microscopic morphology of the cross section of the coating after laser remelting in Example 6 of the present invention.

[0026] Fig. 9 This is a microscopic morphology of the cross section of the coating after laser remelting in Example 8 of the present invention.

[0027] Fig.10 Schematic diagram of Vickers hardness and wear rate of coatings with different boride addition amounts after remelting at 700 W.

[0028] Fig.11 Schematic diagram of Vickers hardness and wear rate of the coating with 10 wt% ZrB2 after remelting with different laser powers.

[0029] Fig.12 Schematic diagram of Vickers hardness and wear rate of the coating with 20 wt% ZrB2 after remelting with different laser powers. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The chemical raw materials required for the present invention can all be purchased from the market.

[0034] A method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating for a boiler water-cooling tube comprises the following steps: The substrate was treated, specifically, the impurities on the substrate were ultrasonically cleaned with anhydrous ethanol to remove impurities such as oil on the substrate surface, and the cleaned substrate was placed in a drying oven for drying. In order to improve the bonding strength between the coating and the substrate, brown corundum sand with a particle size of 24 mesh was used to perform sandblasting roughening treatment on the substrate surface at a pressure of 0.6 MPa, and the sandblasting angle was 60°. The surface roughness of the roughened substrate was controlled to be 2~8 μm. Prepare wear-resistant coating raw materials, the raw materials are commercially available ZrB2 powder and NiCr powder with a purity of 99.99%, the particle sizes of ZrB2 powder and NiCr powder are 45-80 μm and 0.7-1 μm, respectively, the mass proportions of ZrB2 powder and NiCr powder are 1-20% and 80-99%, respectively, and the mass percentages of Ni and Cr in NiCr powder are 80% and 20%, respectively; The raw materials were subjected to ball milling and mixing treatment, wherein the mass ratio of the grinding balls to the raw materials was 1:1; the grinding balls had three different diameters, and the number ratio of the three grinding balls from large to small diameters was 2:5:3, and the rotation speed was 600 r / min; the single operation time was 30 min; the residence time after a single operation was 10 min; the total ball milling time was 8 h; BF-300 binder was added at a uniform speed during the ball milling process to ensure the uniformity of powder coating; the obtained composite powder was dried at a drying temperature of 80°C and a drying time of 6 to 8 h; Atmospheric plasma spraying of NiCr-based composite powder was adopted. Ar gas was used as carrier gas to deliver the dried mixed powder into the center of plasma arc flame flow. The process parameters of atmospheric plasma spraying were as follows: current 500 A, Ar gas flow rate 40 L / min, H2 flow rate 6 L / min, powder feeding rate 2 g / min, spraying distance 100 mm, spray gun moving rate 200 mm / min. In order to prevent the coating from cracking due to large thermal stress, compressed air was used to cool the stainless steel substrate during the spraying process. The thermal spray coating was placed on a temperature field auxiliary heating platform, and the preheating temperature was set at 300℃. After the substrate temperature reached 300℃, the deposited coating was laser remelted to obtain a remelted coating to eliminate defects such as pores and cracks in the unremelted coating. The parameters of the remelting process were set as follows: laser power of 500 W to 900 W, scanning speed of 1000 mm / min, protective gas Ar gas flow rate of 6 L / min, overlap rate of 40%. During the remelting process, an ultrasonic vibration device was used to apply vibration with a frequency of 20 kHz and an amplitude of 5 μm to the stainless steel substrate, and the vibration of the vibration platform was measured using a laser vibrometer.

[0035] Example 1 refer to Figure 1 to Figure 5 , Fig.10 and Fig.11This embodiment provides a method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating for a boiler water-cooling tube, comprising the following steps: (1) Treating the substrate, specifically, using anhydrous ethanol to ultrasonically clean the substrate impurities to remove impurities such as oil on the substrate surface, and placing the cleaned substrate in a drying oven for drying; in order to improve the bonding strength between the coating and the substrate, using brown corundum sand with a particle size of 24 mesh to roughen the substrate surface under a pressure of 0.6 MPa, the sandblasting angle is 60°, and the surface roughness of the roughened substrate is controlled to be 2~8 μm; (2) Prepare the wear-resistant coating raw materials, which are commercially available ZrB2 powder and NiCr powder with a purity of 99.99%. The particle sizes of ZrB2 powder and NiCr powder are 45-80 μm and 0.7-1 μm, respectively. The mass proportions of ZrB2 powder and NiCr powder are 10% and 90%, respectively. The mass percentages of Ni and Cr in NiCr powder are 80% and 20%, respectively. (3) The raw materials were subjected to ball milling and mixing treatment, wherein the mass ratio of the grinding balls to the raw materials was 1:1; the grinding balls had three different diameters, and the number ratio of the three grinding balls from large to small diameters was 2:5:3, and the rotation speed was 600 r / min; the single operation time was 30 min; the residence time after a single operation was 10 min; the total ball milling time was 8 h; BF-300 binder was added at a uniform speed during the ball milling process to ensure the uniformity of powder coating; the obtained composite powder was dried at a drying temperature of 80 °C and a drying time of 8 h; the microscopic morphology of the raw materials was as follows: Figure 3 As shown, after planetary ball milling, small-sized ZrB2 powder is evenly coated on the surface of NiCr powder, and the powder particle size is concentrated in 40~80 μm; (4) Adoption Figure 1 The atmospheric plasma spraying system shown in the figure deposits NiCr-based composite coatings, with the plasma spray gun nozzle as the anode, and a plasma arc as the heat source between the cathode and the anode. When the carrier gas Ar gas passes through the plasma arc, it is heated and ionized to generate high-temperature plasma and form a high-temperature and high-speed plasma flame flow at the nozzle. After the dried NiCr-ZrB2 powder is input into the plasma flame flow, it will be quickly heated to melt and accelerated to 100-300m / s. The high-speed molten particles are sprayed onto the surface of the substrate to form a coating. In order to prevent the high-temperature plasma flame flow from damaging the spray gun, a cooling medium channel for introducing the cooling medium is provided in the spray gun; the process parameters of atmospheric plasma spraying are current 500 A, Ar gas flow rate 40 L / min, H2 flow rate 6 L / min, powder feeding rate 2 g / min, a cooling medium channel is provided in the spray gun to prevent the high-temperature plasma flame flow from damaging the gun body, the spraying distance is 100 mm, and the spray gun moving speed is 200 mm / min. To prevent the coating from cracking due to large thermal stress, compressed air is used to cool the stainless steel substrate during the spraying process. (5) Place the thermal spray coating on Figure 2 On the temperature field assisted laser remelting platform shown, the preheating temperature of the heating plate 3 is set to 300°C. After the substrate temperature reaches 300°C, the laser remelting system remelts the coating to eliminate defects such as pores and cracks. The laser generator 1 outputs a stable high-energy laser beam according to the motion trajectory under the clamping of a six-degree-of-freedom mechanical arm to melt the coating. A protective gas channel for introducing protective gas Ar gas is fixed on the outer wall of the laser generator. During the remelting process, it moves synchronously with the laser generator and outputs Ar gas to protect the coating from oxidation. The parameters of the remelting process are set as follows: laser power of 700W, scanning speed of 1000 mm / min, protective gas Ar gas flow rate of 6 L / min, overlap rate of 40%. During the remelting process, an ultrasonic vibration device 8 placed under the heating plate is used to apply vertical vibration with a frequency of 20 kHz and an amplitude of 5 μm to the stainless steel substrate. The vibration of the vibration platform is measured by a laser vibrometer 7.

[0036] After preparation, let it cool naturally The product coatings were subjected to reciprocating friction and wear tests under the same conditions, where the dual balls were Si3N4 balls with a diameter of 4 mm, a reciprocating frequency of 4 Hz, a sliding load of 20 N, and a friction distance of 1000 m.

[0037] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.387 and the wear rate is 1.72×10 - 6 mm 3 / N·m.

[0038] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the indentation diagonal, and 16 points were selected for each sample in a square array and the average value was calculated. The results showed that the average hardness of the coating was 288.62 HV1.

[0039] from Figure 4 It can be seen that the composite coating after plasma spraying with 10 wt.% ZrB2 has an obvious layered structure with an average thickness of 240 μm. There are obvious holes in the coating cross section, which can be attributed to the peeling of unmelted particles during the spraying process.

[0040] from Figure 5It can be seen that the density of the original coating is significantly improved after laser remelting, the internal pores of the material are significantly reduced, and the microstructure of the coating is more uniform under the assistance of the ultrasonic vibration field. The refined and evenly distributed hard phase is conducive to promoting the improvement of the friction resistance of the coating. In addition, a metallurgical bond is formed between the remelted coating and the substrate, and the bonding strength is greatly improved, which further avoids the coating from peeling off from the substrate during use.

[0041] The invention strengthens the NiCr alloy wear-resistant coating with hard ceramic phase ZrB2, realizes controllable deposition of high-performance wear-resistant coating and regulation of its organizational structure and interface mechanical properties by reasonably setting coating deposition parameters, so as to improve the wear condition of the friction interface.

[0042] Example 2 refer to Figure 1 , Figure 2 , Figure 6 , Figure 7 , Fig.10 and Fig.12 This embodiment provides a method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating for a boiler water-cooling tube. The difference from Example 1 is that the mass proportions of ZrB2 powder and NiCr powder are 20% and 80% respectively. Figure 6 As shown, the amount of small-sized ZrB2 attached to the surface of the composite powder increases with the increase of the added phase content, and the other experimental conditions are the same as those in Example 1. Figure 7 The cross-sectional morphology of the coating after laser remelting is similar to that of Example 1. With the increase of ZrB2 addition, the coating grains tend to be refined, which will help to improve the hardness and wear resistance of the coating.

[0043] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 1, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0044] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.419 and the wear rate is 1.01×10 - 6 mm 3 / N·m.

[0045] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the indentation diagonal, and 16 points were selected for each sample in a square array and the average value was calculated. The results show that the average hardness of the coating is 424.69 HV1.

[0046] Example 3 refer to Figure 1 , Figure 2 and Fig.10 The difference between this embodiment and embodiment 1 is that the mass proportion of ZrB2 powder is 1 wt%, the mass proportion of NiCr powder is 99 wt%, and the other experimental conditions are the same as those in embodiment 1.

[0047] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 1, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0048] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.391 and the wear rate is 2.75×10 - 6 mm 3 / N·m.

[0049] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the diagonal line of the indentation, and 16 points were selected for each sample in a square array and the average value was calculated. The results show that the average hardness of the coating is 210.53 HV1.

[0050] Example 4 refer to Figure 1 , Figure 2 and Fig.11 The difference from Example 1 is that in step (5), the parameter setting power of the remelting process used is 500 W, and the other experimental conditions are the same as those in Example 1.

[0051] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 1, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0052] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.402 and the wear rate is 2.04×10 - 6 mm 3 / N·m.

[0053] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the diagonal line of the indentation, and 16 points were selected for each sample in a square array and the average value was calculated. The results show that the average hardness of the coating is 333.64 HV1.

[0054] Example 5 refer to Figure 1 , Figure 2 and Fig.11 The difference from Example 1 is that in step (5), the parameter setting power of the remelting process used is 900 W, and the other experimental conditions are the same as those in Example 1.

[0055] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 1, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0056] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.394 and the wear rate is 4.34×10 - 6 mm 3 / N·m.

[0057] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the diagonal line of the indentation, and 16 points were selected for each sample in a square array and the average value was calculated. The results show that the average hardness of the coating is 281.54 HV1.

[0058] Example 6 refer to Figure 1 , Figure 2 , Figure 8 and Fig.12 The difference from Example 4 is that the mass proportion of ZrB2 powder is 20wt%, the mass proportion of NiCr powder is 80wt%, and other conditions are the same as Example 4.

[0059] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 4, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0060] The results show that under non-lubricated conditions, the friction coefficient of the prepared coating is 0.386 and the wear rate is 1.59×10 - 6 mm 3 / N·m.

[0061] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the indentation diagonal, and 16 points were selected for each sample in a square array and the average value was calculated. The results show that the average hardness of the coating is 624.74 HV1. Figure 8 The SEM morphology shown in the figure shows that the coating structure after laser remelting is denser and more uniform than that of the atmospheric plasma sprayed coating, so the hardness is greatly improved. However, the phases are not fully melted and there are obvious pore defects in the coating, which can be attributed to the low laser power and the high addition of refractory ZrB2. The defects lead to weaker bonding strength of the coating and higher wear rate.

[0062] Example 7 refer to Figure 1 , Figure 2 and Fig.12 The difference from Example 6 is that the parameter setting power of the remelting process adopted is 900 W, and the other experimental conditions are the same as Example 6.

[0063] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 4, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0064] Under the condition of no lubrication, the friction coefficient of the prepared coating is 0.414 and the wear rate is 2.31×10 -6 mm 3 / N·m.

[0065] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, the distance between the two measuring points was 3 times the length of the diagonal line of the indentation, and 16 points were selected for each sample in a square array and the average value was calculated. Fig.12 As shown, the average hardness of the coating is 375.18 HV1.

[0066] Example 8 refer to Figure 1 , Figure 2 and Fig. 9 The difference from Example 1 is that in step (5), the ultrasonic vibration field applied to the substrate during the remelting process is cancelled, and laser remelting is directly performed after preheating. Other conditions are the same as in Example 1.

[0067] The prepared coating was subjected to a reciprocating friction and wear test, and compared with Example 4, the test was carried out simultaneously under the same conditions, wherein the dual ball was a Si3N4 ball with a diameter of 4 mm, the reciprocating frequency was 4 Hz, the sliding load was 20 N, and the friction distance was 1000 m.

[0068] Compared with the ultrasonic vibration assisted laser remelting coating, the remelting coating without the vibration field has a large number of bubbles on the surface, the internal columnar crystals are coarse and the heat affected zone is significantly widened (reference Fig. 9 ), the improvement of defects such as pores and cracks is not obvious enough. Under the condition of no lubrication, the friction coefficient of the prepared coating is 0.382 and the wear rate is 3.76×10 -6 mm 3 / N·m.

[0069] The hardness of the remelted coating was measured using a HV-10000A Vickers microhardness tester. The applied load was 1000 N, the holding time was 15 s, and the distance between the two measuring points was 3 times the length of the diagonal of the indentation. 16 points were selected for each sample in a square array and the average value was calculated. The results showed that the average hardness of the coating was 266.78 HV1.

[0070] The wear rate is usually proportional to the hardness of the material. By comprehensively comparing the wear rate, Vickers hardness and bonding strength of the coating in the above embodiments, it is not difficult to find that Example 2 is the best implementation method. The use of the present invention significantly improves the wear resistance of the boiler water-cooling pipe while not affecting the heat exchange efficiency of the water-cooling system. The coating can well meet the requirements of the wear resistance of the water-cooling pipe wall in the fly ash erosion environment.

[0071] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a ceramic particle reinforced high-temperature alloy wear-resistant coating for a boiler water-cooling tube. Its characteristics are At: The following steps are included: Roughening the substrate; The prepared NiCr powder and ZrB2 powder are mixed by high-energy ball milling, and dried after treatment to obtain a dried NiCr-based composite powder; The NiCr-based composite powder is sprayed by atmospheric plasma to deposit a composite coating with a thickness of 200 to 300 μm on the roughened substrate surface; The composite coating is subjected to a remelting treatment to form a remelted coating on the surface of the substrate; The matrix is ​​304 stainless steel, and the composition ratios of NiCr powder and ZrB2 powder are 80-99 wt% NiCr and 1-20 wt% respectively.

2. The preparation method according to claim 1, characterized in that: The specific steps of the roughening process are: The impurities of the substrate are ultrasonically cleaned with anhydrous ethanol, and then dried and sandblasted to obtain a sandblasted and roughened substrate.

3. The preparation method according to claim 2, characterized in that: The sandblasting roughening treatment uses brown corundum sand with a particle size of 24 mesh, the sandblasting pressure is 0.6 MPa, the sandblasting angle is 60°, and the roughness of the substrate after roughening is controlled at 2~8 μm.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The ball milling was carried out using a planetary ball milling method. The mass ratio of grinding balls to powder was 1:

1. Three grinding balls with different diameters were used. The number ratio of the three grinding balls from large to small diameters was 2:5:

3. The rotation speed was 600 r / min. The residence time after a single operation was 10 min. The total ball milling time was 8 h. BF-300 binder was added at a uniform speed during the ball milling process.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The average particle size of the NiCr powder is 45-80 μm, and the average particle size of the ZrB2 powder is 0.7-1 μm.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The drying temperature is 80° C. and the drying time is not less than 6 h.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The parameters of the atmospheric plasma spraying are: current 500 A, Ar gas flow rate 40 L / min, H2 flow rate 6 L / min, powder feeding rate 2 g / min, spraying distance 100 mm, spray gun moving rate 200 mm / min, and compressed air is used to cool the stainless steel substrate during the spraying process.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The method also includes the following steps: placing the atmospheric plasma sprayed coating on a temperature field auxiliary heating platform, setting the heating temperature to 300° C. and performing laser remelting treatment on the coating at this temperature.

9. The preparation method according to claim 8, characterized in that: During the laser remelting process, a vibration with a frequency of 20 kHz and an amplitude of 5 μm was applied to the stainless steel substrate.

10. The preparation method according to claim 9, characterized in that: During the laser remelting process, the laser power was 500-900 W, the scanning speed was 1000 mm / min, the overlap rate was 40%, and Ar gas with a flow rate of 6 L / min was introduced as a protective gas during the remelting process. The remelted coating was slowly cooled to room temperature along with the heating platform.

Citation Information

Patent Citations

  • Preparation method of high-efficiency, low-dilution-rate coating for boiler water-cooled wall tube bank

    CN111690928B

Cited By

  • High-thickness and high-purity MAX phase coating and preparation method thereof

    CN121204596A

  • Laser-induced plasma assisted deposition thermal barrier coating and preparation method thereof

    CN121575344A

  • Laser-induced plasma-assisted deposition of thermal barrier coatings and methods of making the same

    CN121575344B

  • Anti-oxidation coating of high-pressure hot-pressing mold and preparation method of anti-oxidation coating

    CN121992344A